Verbal violence against women on TikTok: A feminist linguistic study - Dewanty, Imanuella Anastasia Brigitha Carneliaputri; Saryono, Djoko (LITERA, 2024)
This article explores verbal violence against women on TikTok to uncover the underlying factors contributing to the verbal violence. Using a qualitative approach, we examine verbal violence on the @bacotinajagpp TikTok account from March 2022 to December 2023. The analysis is grounded in feminist theory in Linguistics, which examines how language perpetuates gender-based oppression and reinforces patriarchal norms. Methodologically, the study utilizes a qualitative content analysis of TikTok posts to identify patterns in language use and strategies of verbal violence. The findings show that verbal violence represented in the language used in the account can be categorized into four types (sexual, appearance-related, intellectual, and character-based), manifested in five language variations (hate speech, abusive language, offensive language, aggressive language, and harassing language) and articulated through four strategies (general statements, personal attacks, intimidation, and manipulation). These patterns underscore the use of verbal violence to reinforce men's social dominance by threatening, insulting, and demeaning women, thereby perpetuating negative stereotypes. This article aims to raise awareness of these issues to reduce verbal violence on social media and mitigate negative stereotypes about women. By doing so, the study seeks to cultivate a more respectful online environment and diminish misogynistic attitudes.